2018
DOI: 10.1017/s1352465818000401
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation into the Effect of State-Anxiety on State-Paranoia in People Experiencing Psychosis

Abstract: State-anxiety and negative-affect may both be involved in the maintenance of paranoia in clinical populations, as predicted by cognitive models. Negative-affect may be the strongest predictor of state-paranoia in clinical populations. Reasons for this are discussed, as well as the implications. Interventions that seek to reduce negative state-affect may be beneficial in managing state-paranoia. Further research is warranted to explore the suggested clinical and theoretical implications of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In turn, state and trait anxiety was found to intercorrelate in a sample of patients with schizophrenia (Guillem, Pampoulova, Stip, Lalonde & Todorov, 2005) and schizophrenia patients tend to score higher in STAI measures than controls (Jansen et al, 2000). While state anxiety is thought more of as an effect of psychosis (Guillem et al, 2005) and has been demonstrated to be a predictor of state-paranoia (Cowles & Hogg, 2019), trait and state anxiety was shown to be related with positive symptoms of schizophrenia, such as bizarre delusions and auditory hallucinations (Guillem et al, 2005). Importantly, both anxiety measures affect cognitive control and attentional processes in controls (Pacheco-Unguetti, Acosta, Callejas & Lupiáñez, 2010).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In turn, state and trait anxiety was found to intercorrelate in a sample of patients with schizophrenia (Guillem, Pampoulova, Stip, Lalonde & Todorov, 2005) and schizophrenia patients tend to score higher in STAI measures than controls (Jansen et al, 2000). While state anxiety is thought more of as an effect of psychosis (Guillem et al, 2005) and has been demonstrated to be a predictor of state-paranoia (Cowles & Hogg, 2019), trait and state anxiety was shown to be related with positive symptoms of schizophrenia, such as bizarre delusions and auditory hallucinations (Guillem et al, 2005). Importantly, both anxiety measures affect cognitive control and attentional processes in controls (Pacheco-Unguetti, Acosta, Callejas & Lupiáñez, 2010).…”
Section: Discussionmentioning
confidence: 93%
“…There is a complex relationship between anxiety and positive symptom expression in psychotic states. Trait and state anxiety (STAI;Spielberger et al, 1983) can be seen as predictors of paranoia in psychosis spectrum disorders (Freeman & Fowler, 2009;Cowles & Hogg, 2019), whereas state anxiety mediates intrusive thoughts in hallucinating schizophrenia patients (Bortolon, Capdevielle & Raffard, 2015). Previous reports have shown that trait anxiety is significantly associated with positive psychotic symptoms and auditory hallucinations in schizophrenia patients, making it a potential causal factor for the disorder (Guillem et al, 2005).…”
mentioning
confidence: 99%
“…Additionally, the high rate of comorbidity between anxiety and schizophrenia spectrum disorders was highlighted in some studies (Achim et al, 2011;Temmingh & Stein, 2015). High levels of anxiety are associated with the onset of paranoid episodes (Thewissen et al, 2011;Cowles & Hogg, 2019), more conviction of delusional beliefs (Garety et al, 2005), further delusion-induced distress (Startup, Freeman & Garety, 2007), and greater use of safety behaviors and avoidance in patients with delusion (Freeman, Ga-rety & Kuipers, 2001). Bortolon & Raffard (2015) indicated that anxiety mediates the delusion-like experiences in patients with Obsessive-Compulsive Disorder (OSD); as anxiety rises, OCD symptoms become more similar to delusion-like experiences.…”
Section: Introductionmentioning
confidence: 99%